2004
DOI: 10.1158/0008-5472.can-03-1735
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein Prevents Human Breast Carcinoma Cell Line from Tumor Necrosis Factor α-Induced Cell Death

Abstract: To define genetic determinants of tumor cell resistance to the cytotoxic action of tumor necrosis factor ␣ (TNF), we have applied cDNA microarrays to a human breast carcinoma TNF-sensitive MCF7 cell line and its established TNF-resistant clone. Of a total of 5760 samples of cDNA examined, 3.6% were found to be differentially expressed in TNF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 33 publications
2
99
0
3
Order By: Relevance
“…To determine if the antiBax function of PrP is specific to human neurons, we studied MCF-7 cells, where PrP was found to protect against TNFainduced cell death. 7 PrP maintains its protection against Baxmediated cell death in the MCF-7 cells as does Bcl-2, allowing us to use these as a model cell line to study the effects of PrP (Figure 1b). We then investigated if PrP could prevent cell death mediated by tBid, a BH3-only proapoptotic Bcl-2 protein that activates both Bax and Bak.…”
Section: Prp Prevents Bax But Not Bak-or Tbid-mediated Cell Death In mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if the antiBax function of PrP is specific to human neurons, we studied MCF-7 cells, where PrP was found to protect against TNFainduced cell death. 7 PrP maintains its protection against Baxmediated cell death in the MCF-7 cells as does Bcl-2, allowing us to use these as a model cell line to study the effects of PrP (Figure 1b). We then investigated if PrP could prevent cell death mediated by tBid, a BH3-only proapoptotic Bcl-2 protein that activates both Bax and Bak.…”
Section: Prp Prevents Bax But Not Bak-or Tbid-mediated Cell Death In mentioning
confidence: 99%
“…1,2 PrP prevents anisomycin-mediated cell death in the neuroblastic layer of mouse retinal explants, 3,4 Doppel-and N-terminally truncated PrP-induced neurodegeneration in mice, 5,6 and tumor necrosis factor a (TNFa)-induced apoptosis in MCF-7 cells. 7 We have shown that both wild-type and cytosolic PrP completely inhibit Bcl-2-associated protein X (Bax)-mediated cell death in human neurons in primary cultures. 8,9 However, whether PrP inhibits upstream or downstream of Bax activation is not known.…”
Section: Introductionmentioning
confidence: 99%
“…PrP also binds Grb2, an adapter protein, lipids, and nucleic acids (15)(16)(17). PrP plays a role in apoptosis in a cell context-dependent manner (18)(19)(20)(21)(22). PrP is involved in the proliferation of epithelial cells and in the distribution of junction associated proteins in human enterocytes in vitro and in intestine in vivo (23).…”
Section: Introductionmentioning
confidence: 99%
“…8). It has been reported that PrP c protects against tumor necrosis factor ␣- (9) and Bax-induced cell death (10,11), although this phenotype varies according to the cell type (12). Conversely, we recently established that PrP c overexpression led to an increased staurosporine-evoked cell death (13) in transfected or inducible cell lines and showed that this cellular response was associated with an activation of caspase-3 linked to a transcriptional and post-transcriptional control of the p53 transcription factor (14).…”
mentioning
confidence: 99%